Pemberdayaan Masyarakat Desa Banjarsari Melalui Edukasi Apoteker Cilik, Skrining Kesehatan, Dan Pemanfaatan Tanaman Herbal Untuk Mewujudkan Desa Sehat - Latief, Mutawalli Sjahid; Kurniawan, David; Mardikayasa, I Ketut; Oktaviani, Nabilla (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The level of health education in rural communities, particularly regarding the use of medication and the utilization of herbal remedies, remains relatively low. Children, as the next generation, play a strategic role in disseminating health information within their families. This Community Service Program (KKN) was carried out over three days, from December 12 to 14, 2024, in Banjarsari Village, Ciawi Subdistrict, Bogor Regency. The program aimed to enhance health education for elementary school students through the Junior Pharmacist program, as well as for the general public through health screenings and herbal juice preparation training as an alternative to promote a healthy lifestyle. The methods included interactive educational sessions with pre- and post-tests, blood pressure, blood glucose, and cholesterol screenings, as well as practical training in herbal processing. The results showed a significant increase in students’ understanding of the pharmacist profession, rising from 40% to 90% after the intervention. Health screenings identified previously undiagnosed cases of hypertension and hypercholesterolemia. In addition, the herbal juice training featuring garlic, lemon, ginger, honey, and apple cider vinegar received positive feedback from residents as an alternative health solution. This activity not only improved knowledge but also raised community awareness regarding the importance of a healthy lifestyle and rational use of medicine. Community-based education and empowerment proved effective in fostering health awareness from an early age.